The Role of the Four-Wheel Dialogical Patrol Unit of the Turjawali Satsabhara in Preventing the Crime of Theft with Aggravated Circumstances in Blitar City Police Jurisdiction - Rizal Gulam (Police Studies Review, 2021)
The rise of theft with aggravated circumstances (Curat) which is troubling the community has caused disturbances in public order. The police as the protectors of the community try to maintain kamtibmas through four-wheeled dialogue vehicle patrols. The role of this patrol is very important in preventing spouts. This study aims to describe the picture of drains, describe the role of the Satsabhara dialogic four-wheel patrol and identify the factors that influence the dialogical four-wheel patrol in preventing scurvy at the Blitar City Police. The theory used in this research is Routine Activity Theory and Management Theory. Furthermore, the concepts used are four-wheel patrol, dialogical patrol, drain, kamtibmas, and Perkabaharkam No. 1 of 2017. This research was conducted using a qualitative approach with field research methods. Data were collected through interviews, observations, and document studies, as well as data validity using data triangulation. The results of the study found that the purposive case was the most prominent case in the Blitar City Police Station. Satsabhara's four-wheeled dialogical patrol role in preventing Curat is not optimal because deficiencies still exist at every stage. The inhibiting factors are human resources, patrol targets, involvement in the Yustisi Operations. While the supporting factors are facilities and infrastructure, teamwork and community factors. In increasing the role of the four-wheeled dialogical patrol of the Turjawali Satsabhara unit, special training is needed for members of the Turjawali unit, reactivating the "Jogo Bumi Proklamator" application, and increasing cooperation and coordination between technical functions, especially with the detective function through Kring Serse in preventing Curat.